The travel book : a journey through every country in the world (Lonely Planet Ltd, 2024)
A pictorial guide to travel around the world features 680 full-color photographs and descriptions of 200 countries, all organized alphabetically for easy access, along with key facts, maps, cultural insights, and travel tips for each nation.